Automated extraction of meandering river morphodynamics from multitemporal remotely sensed data. (July 2018) - Monegaglia, Federico; Zolezzi, Guido; Güneralp, Inci; Henshaw, Alexander J.; Tubino, Marco
Abstract: We introduce P yRIS, an automated, process-based software for extracting extensive meandering and anabranching river morphodynamics from multitemporal satellite imagery, including a unique ability to quantify river bars dynamics. P yRIS provides three main computations: (i) detection of planform centerline including complex river patterns, (ii) computation of migration vectors between subsequent centerlines, and (iii) analysis of sediment bars dynamics. P yRIS was validated against several test cases in the Amazon River basin, specifically i) main channel extraction from the anabranching Amazon river, ii) migration analysis following a large cutoff on the Ucayali River and iii) detection of sediment bar migration on the Xingu River. Tests prove the capability of P yRIS to detect the main channel in anabranching structures and chute cutoffs. P yRIS can extract extensive morphodynamic information with unprecedented automation levels and reasonable computational effort (5 h for 28 Landsat images of a 240 km reach of the Xingu River on a 3.20 GHz Intel). Graphical abstract: Image 1 Highlights: Automated software to extract meandering planform from Landsat data. Multitemporal analysis of river morphodynamics for large rivers. First automated procedure to investigate multitemporal sediment bar dynamics. Novel algorithm for the direction and rate of channel migration. Suitable for anabranching rivers: recognizes main channel at bifurcations.